The third All-Russian Congress of Trade Unions. Resolutions and regulations. With an introd. by A. Losovsky [A. Lozovskij (Ps., von S.A. Dridzo)] (Moscow, 1920)
Publ. by the All-Russian Central Council of Trade Unions.